Impact of a high-risk multimorbidity integrated care implemented at the public health system in Chile. - Paula Zamorano; Paulina Muñoz; Manuel Espinoza; Alvaro Tellez; Teresita Varela; Francisco Suarez; Maria Jose Fernandez (PLoS ONE, 2022)
During recent years, multimorbidity has taken relevance because of the impact of causes in the system, people, and their families, which has been a priority in the health care plan. Interventions strategies and their implementation are still an emerging topic. In this context, Centro de Innovación en Salud ANCORA UC, together with Servicio de Salud Metropolitano Sur Oriente, implemented as a pilot study High-Risk Multimorbidity Integrated Care strategy. This study aimed to evaluate the impact of this strategy in terms of health services utilization and mortality. A cohort study was conducted with high-risk patients with multimorbidity, stratified by ACG®, intervened between April 2017 and December 2019. The studied population was 3,933 patients who belonged to similar size and location primary care centers. The impact analysis was performed used generalized linear models. Results showed that intervened patients had a significantly lower incidence in mortality (OR 0.56; 95% CI 0.40-0.77), hospital admissions, length of stay, and the number of hospital emergency consultancies. With the proper barriers and facilitators of a real context intervention, the implementation process allowed the systematization and consolidation of the intervention provided in this study. The training for new roles and the constant implementation support from the Centro de Innovación en Salud ANCORA UC team were essential in the progress and success of the intervention. A complete description of the high-risk intervention strategy is provided to contribute to this emerging topic and facilitate its scale-up. We can conclude that this complex intervention was feasible to be implemented in a real context. The Ministry of Health has taken the systematization and consolidation of the conditions for the national scale-up.